2021
DOI: 10.3390/biom11121771
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs Regulating Renin–Angiotensin–Aldosterone System, Sympathetic Nervous System and Left Ventricular Hypertrophy in Systemic Arterial Hypertension

Abstract: MicroRNAs are small non-coding RNAs that regulate gene and protein expression. MicroRNAs also regulate several cellular processes such as proliferation, differentiation, cell cycle, apoptosis, among others. In this context, they play important roles in the human body and in the pathogenesis of diseases such as cancer, diabetes, obesity and hypertension. In hypertension, microRNAs act on the renin–angiotensin–aldosterone system, sympathetic nervous system and left ventricular hypertrophy, however the signaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 84 publications
0
6
0
Order By: Relevance
“…At present, abnormal lipid metabolism leading to left ventricular hypertrophy was explained by the accumulation of lipids in or around myocytes. A study on the human heart showed that fat deposition in the left ventricle constituted a direct risk of myocardial hypertrophy 34 ; abnormal lipid metabolism can be manifested by strong systemic or local inflammation and mitochondrial oxidative stress 35 and/or increased production of reactive oxygen species in NADPH oxidase complex, resulting in oxidative modification of LDL, thereby amplifying the inflammatory potential 36 ; abnormal lipid metabolism was usually accompanied by insulin resistance in the animal model of high‐fat feeding 37 and promoted LVH 38 ; neurohumoral effects 39 included the effects of the sympathetic nervous system, 9 renal angiotensin aldosterone system (RAAS), and other hormones. In addition, other signaling pathways caused by dyslipidemia also played important roles in the development of myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…At present, abnormal lipid metabolism leading to left ventricular hypertrophy was explained by the accumulation of lipids in or around myocytes. A study on the human heart showed that fat deposition in the left ventricle constituted a direct risk of myocardial hypertrophy 34 ; abnormal lipid metabolism can be manifested by strong systemic or local inflammation and mitochondrial oxidative stress 35 and/or increased production of reactive oxygen species in NADPH oxidase complex, resulting in oxidative modification of LDL, thereby amplifying the inflammatory potential 36 ; abnormal lipid metabolism was usually accompanied by insulin resistance in the animal model of high‐fat feeding 37 and promoted LVH 38 ; neurohumoral effects 39 included the effects of the sympathetic nervous system, 9 renal angiotensin aldosterone system (RAAS), and other hormones. In addition, other signaling pathways caused by dyslipidemia also played important roles in the development of myocardial hypertrophy.…”
Section: Discussionmentioning
confidence: 99%
“…Several miRNAs regulate renin–angiotensin–aldosterone system genes. In addition, it is described that the miRNA expression is altered in hypertensive human patients [ 104 ]. MiR-136 was significantly downregulated in peripheral blood serum of hypertensive patients [ 105 ].…”
Section: Micrornas In the Diagnosis Of Cardiovascular Diseasesmentioning
confidence: 99%
“…Infection of the organism with a virus or parasite also modi es the expression of miRNAs, as in HIV [18] and Chagas disease [19,20]. Several miRNAs have been described deregulated in H [21][22][23], T2DM [24][25][26] and OB [27,28]. Among these, miRNA-1 (miR-1) [29], miRNA-21 (miR-21) [30] and miRNA-126 (miR-126) [31] have been highlighted.…”
Section: Introductionmentioning
confidence: 99%